Scalable Biomimetic Coaxial Aligned Nanofiber Cardiac Patch: A Potential Model for “Clinical Trials in a Dish” - Kumar, Naresh; Sridharan, Divya; Palaniappan, Arunkumar; Dougherty, Julie A.; Czirok, Andras; Isai, Dona Greta; Mergaye, Muhamad; Angelos, Mark G.; Powell, Heather M.; Khan, Mahmood (Frontiers in Bioengineering and Biotechnology, 2020)
Recent advances in cardiac tissue engineering have shown that human induced-pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) cultured in a three-dimensional (3D) micro-environment exhibit superior physiological characteristics compared with their two-dimensional (2D) counterparts. These 3D cultured hiPSC-CMs have been used for drug testing as well as cardiac repair applications. However, the fabrication of a cardiac scaffold with optimal biomechanical properties and high biocompatibility remains a challenge. In our study, we fabricated an aligned polycaprolactone (PCL)-Gelatin coaxial nanofiber patch using electrospinning. The structural, chemical, and mechanical properties of the patch were assessed by scanning electron microscopy (SEM), immunocytochemistry (ICC), Fourier-transform infrared spectroscopy (FTIR)-spectroscopy, and tensile testing. hiPSC-CMs were cultured on the aligned coaxial patch for 2 weeks and their viability [lactate dehydrogenase (LDH assay)], morphology (SEM, ICC), and functionality [calcium cycling, multielectrode array (MEA)] were assessed. Furthermore, particle image velocimetry (PIV) and MEA were used to evaluate the cardiotoxicity and physiological functionality of the cells in response to cardiac drugs. Nanofibers patches were comprised of highly aligned core-shell fibers with an average diameter of 578 ± 184 nm. Acellular coaxial patches were significantly stiffer than gelatin alone with an ultimate tensile strength of 0.780 ± 0.098 MPa, but exhibited gelatin-like biocompatibility. Furthermore, hiPSC-CMs cultured on the surface of these aligned coaxial patches (3D cultures) were elongated and rod-shaped with well-organized sarcomeres, as observed by the expression of cardiac troponin-T and α-sarcomeric actinin. Additionally, hiPSC-CMs cultured on these coaxial patches formed a functional syncytium evidenced by the expression of connexin-43 (Cx-43) and synchronous calcium transients. Moreover, MEA analysis showed that the hiPSC-CMs cultured on aligned patches showed an improved response to cardiac drugs like Isoproterenol (ISO), Verapamil (VER), and E4031, compared to the corresponding 2D cultures. Overall, our results demonstrated that an aligned, coaxial 3D cardiac patch can be used for culturing of hiPSC-CMs. These biomimetic cardiac patches could further be used as a potential 3D in vitro model for “clinical trials in a dish” and for in vivo cardiac repair applications for treating myocardial infarction.